Discovery and characterization of bioactive cysteine-rich peptides in medicinal plants - Tang, Fan (Nanyang Technological University, 2023)
Plants produce an enormously diverse range of medicinally useful molecules, ranging from small-molecule metabolites to peptides, microproteins, proteins, and biopolymers. Among them, plant-derived peptides are not only under-explored, but also marginalized for their unstable stereotypes. This thesis describes my discovery and characterization of two highly stable and novel peptides, wisotide (wS1) from Withania somnifera and wuweizitide (wZ1) from Schisandra chinensis. Both wZ1 and wS1 belong to the superfamily of cysteine-rich peptides (CRPs) whose structures are stabilized by multiple cross braces of disulfides. Indeed, the structures of the two CRPs were elucidated and confirmed using NMR spectroscopy. In addition, they are highly resistant to proteolytic degradation. These desirable properties share similarities to small-molecule metabolites as drug-like molecules and dispel the misconception that peptides are inherently unstable. Sequencing by mass spectrometry showed that wS1, with eight cysteines, contains 31 amino acids. Structural determination by NMR showed that wS1 displays the lybatide-like disulfide connectivities to support helical conformations. The helical conformation is a common structure motif found in proteins but rare in short peptides. Peptide stapling is a synthetic strategy to constrain the helical conformations of a short peptide, generally through covalent linkage of their side chains. They are also known to be cell-membrane permeable and capable of inhibiting intracellular protein-protein interactions. However, naturally-occurring stapled peptides are rare. Previously, we discovered lybatides which contain helices stapled by cystine. Moreover, lybatides form a new family of cysteine-rich peptides with novel disulfide connectivity. Here, my thesis shows that wS1 is the second member of cystine-stapled helical peptides. Importantly, the anionic cystine-stapled wS1 is cell-membrane permeable. Database mining further revealed that >50 lybatide/wS1-like sequences are found in plants. Taken together, wS1 and the cystine-stapled helical peptides could represent useful leads of peptide biologics to probe intracellular protein-protein interactions. Wuweizitide (wZ1) was found to contain 18 residues with six cysteines, giving wZ1 a 33% cysteine content. This hyperdisulfide peptide is also hyperstable and cell-membrane permeable. This thesis shows that wZ1 induces LDL uptake by an atypical mechanism of LDLR accumulation at lipid rafts, suggesting that it might lower circulating LDL-cholesterol by a novel mechanism. These findings not only expand our knowledge and understanding of CRP families, but also open new avenues for discovering hyperstable bioactive peptides as leads for orally-active therapeutics from medicinal plants.